Method for prediction of vapor pressure for isotopes and isotope-containing gases. (December 2020) - Münch, Benjamin; Alekseev, Alexander; Petraglia, João Miguel; Fritsch, Philipp; Klein, Harald
Highlights: A method for prediction of vapor pressure for isotopes of cryogenic substances. Can be applied to classic cryogenic substances like oxygen, nitrogen, argon, neon, carbon monoxide. (Worldwide first) publishing of critical parameters for three cryogenic isotopic substances – 13C16O, 12C18O and 12C16O. Abstract: Stable isotopes of light elements, such as 13 C, 18 O and 15 N are used as markers in medicine, pharmacy, biology and other sciences. The demand for isotopes is continuously rising. It will lead to the extension of existing production capacities in the next years and could trigger the development of corresponding processes and systems. The most important issue concerns the optimization of the isotopes production costs. It would be a key factor for the establishment and commoditization of isotope-based methods for everyday life and could improve the quality of health care worldwide. The most economical approach to industrial scale production of stable isotopes is the cryogenic distillation. This method uses the difference in substances' vapor pressures for separation purposes. But only limited data on the vapor pressure curves of isotopes is currently available, which affects the development of new processes. A new method to predict vapor pressures for stable isotopes is described in the present work. The method is based on a combination of the theory of corresponding states with limited experimental data on the vapor pressure ratios of isotopes available in the literature. This method allows to generate parameters like the critical temperature and pressure for isotopes and isotope-containing gases. In the present work this method is applied to carbon monoxide based on the carbon isotopes.